Barriers and prospects of India's conditional cash transfer program to promote institutional delivery care: a qualitative analysis of the supply-side perspectives - Adyya Gupta; Jasmine Fledderjohann; Hanimi Reddy; V. R. Raman; David Stuckler; Sukumar Vellakkal (BMC, 2018)
Abstract Background Under the National Health Mission (NHM) of India, Janani Suraksha Yojana (JSY) offers conditional cash transfer and support services to pregnant women to use institutional delivery care facilities. This study aims to understand community health workers' (ASHAs) and program officials' perceptions regarding barriers to and prospects for the uptake of facilities offered under the JSY. Methods Fifty in-depth interviews of a purposively selected sample of ASHAs (n = 12), members of Village Health and Sanitation Committees (n = 11), and officials at different tiers of healthcare facilities (n = 27) were conducted in three Indian states. The data were analyzed thematically using ATLAS.ti software. Results Although the JSY has triggered considerable advancement on the Indian maternal and child health front, there are several barriers to be resolved pertaining to i) delivering quality care at health-facility; ii) linkages between home and health-facility; and iii) the community/household context. At the facility level, respondents cited an inability to treat birth complications as a barrier to JSY uptake, resulting in referrals to other (mostly private) facilities. Despite increased investment in health infrastructure under the program, shortages in emergency obstetric-care facilities, specialists and staff, essential drugs, diagnostics, and necessary equipment persisted. Weaker linkages between various vertical (standalone) elements of maternal and primary healthcare programs, and nearly uniform resource allocation to all facilities irrespective of caseloads and actual need also constrained the provision of quality healthcare. Barriers affecting the linkages between home and facility arose mainly due to the mismatch between the multiple demands and the availability of transport facilities, especially in emergency situations. Regarding community/household context, several socio-cultural issues such as resistance towards the ASHA's efforts of counselling, particularly from elderly family members, often adversely affected people's decision to seek healthcare. Conclusion Adequate interventions at the community level, capacity building for healthcare providers, and measures to address underlying structural and systemic barriers are needed to improve the uptake of institutional maternal healthcare.